Oral surgery in a patient with sickle cell anemia: a literature review (Research, Society and Development, 2023)
Sickle cell anemia is one of the most recurrent hemoglobinopathies in the world, being a hereditary disease where red blood cells are sickle-shaped. The objective of this study was to identify the ideal conduct for performing surgical procedures in patients with sickle cell anemia. A literature review was performed with a search in the PubMed, Scielo and BVS databases and, after selection and analysis of the inclusion and exclusion criteria, 20 articles were included in the review. The literature shows that during the clinical examination the dentist must evaluate the oral cavity as a whole and be attentive to the oral manifestations that are presented in it, oral surgery requires knowledge that goes beyond prevention and diagnosis, the management of the case from the preoperative period will be decisive in the case and aims to identify the ideal conduct for surgical procedures in patients with sickle cell anemia. General antibiotic prophylaxis is necessary to prevent the triggering of bacterial endocarditis. Finally, care should be provided for a period of time without seizures and therapy should be directed to palliative treatment.